1969
DOI: 10.1128/jb.98.2.388-393.1969
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Sodium in the Anaerobic Growth of Aerobacter aerogenes on Citrate

Abstract: Anaerobic growth of Aerobacter aerogenes on citrate as a carbon source required the presence of Na+. The growth rate increased with increasing Na+ concentration and was optimal at 0.10 M Na+. The requirement was specific for Na+, which could not be replaced by K+, NH4+, Li+, Rb+, or Cs+. K+ was required for growth in the presence of Na+, the optimal K+ concentration being 0.15 mm. Enzyme profiles were determined on cells grown in three different media: (i) intermediate Na+, high K+ concentration, (ii) high Na+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

1973
1973
1992
1992

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…The amount of NAD(P)H produced from citrate oxidation is probably insufficient to meet the biosynthetic demands, because 2-oxoglutarate dehydrogenase is repressed under anaerobic conditions (O'Brien and Stern, 1969) and succinate is not formed as fermentation product (see above).…”
Section: How Reducing Equivalents May Be Formed During the Fermentatimentioning
confidence: 99%
“…The amount of NAD(P)H produced from citrate oxidation is probably insufficient to meet the biosynthetic demands, because 2-oxoglutarate dehydrogenase is repressed under anaerobic conditions (O'Brien and Stern, 1969) and succinate is not formed as fermentation product (see above).…”
Section: How Reducing Equivalents May Be Formed During the Fermentatimentioning
confidence: 99%
“…In regard to the effects of O 2, it is of considerable interest that regulation of KGD synthesis shows features in common with the controls affecting succinate~ fumarate interconversions. Thus, in amphiaerobes, KGD synthesis appears to be induced by O 2 and is repressed during anaerobic growth [30][31][32]. Keevil et al [33] have recently reported that even trace concentrations of 02 (approx.…”
Section: Regulation Of A-ketoglutarate Dehydrogenasementioning
confidence: 99%
“…In E. aerogenes and K. pneumoniae citrate can serve as the sole source of carbon and energy only in the presence of Na + under anaerobic conditions. Hence, Na + is essential for the anaerobic growth of these bacteria on citrate [89,100,101]. In the presence of citrate, citrate lyase and oxaloacetate decarboxylase are induced and the tricarboxylic acid cycle is turned off [102].…”
Section: Physiology and Enzymology Of Citrate Metabolismmentioning
confidence: 99%
“…Oxaloacetate is, therefore, decarboxylated to pyruvate by oxaloacetate decarboxylase whose activity is Na+-dependent [103]. Oxaloacetate is then converted to acetyl-CoA via pyruvate formate lyase [9,89]. Acetyl-CoA functions as a source for the generation of reducing power and ATP.…”
Section: Physiology and Enzymology Of Citrate Metabolismmentioning
confidence: 99%
See 1 more Smart Citation